The Effect of Visual Stimuli on Stability and Complexity of Postural Control - Luo, Haizhen; Wang, Xiaoyun; Fan, Mengying; Deng, Lingyun; Jian, Chuyao; Wei, Miaoluan; Luo, Jie (Frontiers in Neurology, 2018)
Visual input could benefit balance control or increase postural sway, and it is far from fully understanding the effect of visual stimuli on postural stability and its underlying mechanism. In this study, the effect of different visual inputs on stability and complexity of postural control was examined by analyzing the mean velocity (MV), standard deviation (SD), and fuzzy approximate entropy (fApEn) of the center of pressure (COP) signal during quiet upright standing. We designed five visual exposure conditions: eyes-closed (EC), eyes-open (EO), and three virtual reality scenes (VR1-VR3). The VR scenes were a limited field view of an optokinetic drum rotating around yaw (VR1), pitch (VR2) and roll (VR3) axis, respectively. Sixteen healthy subjects were involved in the experiment, and their COP trajectories were assessed from the force plate data. MV, SD, and fApEn of the COP in anterior-posterior (AP), medial-lateral (ML) directions were calculated. Two-way analysis of variance with repeated measures was conducted to test the statistical significance. We found that all the three parameters obtained the lowest values in the EO condition, and highest in the VR3 condition. We also found that the active neuromuscular intervention, indicated by fApEn, in response to changing the visual exposure conditions were more adaptive in AP direction, and the stability, indicated by SD, in ML direction reflected the changes of visual scenes. MV was found to capture both instability and active neuromuscular control dynamics. It seemed that the three parameters provided compensatory information about the postural control in the immersive virtual environment.